ОЦІНЮВАННЯ МАКРОЕКОНОМІЧНИХ ЧИННИКІВ ФОРМУВАННЯ ФІНАНСОВОЇ БЕЗПЕКИ УКРАЇНИ - Кириленко, Ольга Павлівна; Стащук, Олена Володимирівна (Науковий журнал «Світ фінансів», 2017)
Кириленко О. П., Стащук О. В. Оцінювання макроекономічних чинників формування фінансової безпеки України. Визначено місце фінансової безпеки в системі економічної безпеки країни, проаналізовано основні теоретичні підходи до трактування поняття “фінансова безпека держави” та відображено основні її складові. Виокремлено показники оцінювання рівня фінансової безпеки держави. Досліджено релевантні макроекономічні чинники, що впливають на забезпечення стану фінансової безпеки, проведено оцінку тенденцій зміни таких чинників в Україні протягом 2012–2015 рр. Запропоновано напрямки підвищення рівня фінансової безпеки в Україні. Кириленко О. П., Стащук Е. В. Оценка макроэкономических факторов формирования финансовой безопасности Украины. Определено место финансовой безопасности в системе экономической безопасности страны, проанализированы основные теоретические подходы к трактовке понятия “финансовая безопасность государства”, отражены основные ее составляющие. Выделены показатели оценки уровня финансовой безопасности государства. Исследованы релевантные макроэкономические факторы, влияющие на обеспечение состояния финансовой безопасности, проведена оценка тенденций изменения этих факторов в Украине в течение 2012–2015 гг. Предложены направления повышения уровня финансовой безопасности в Украине. Kyrylenko O., Stashchuk O. Evaluation of macroeconomic factors formation of financial security of Ukraine.Introduction. The financial security of the state is one of the most important components of economic security in general and in terms of its individual functional elements. The financial security of the country determines the level of attractiveness, competitive position in world markets and creates conditions for economic development of certain entities in prospective periods.The purpose of the paper is to determine the place of financial security in the economic security of the country, the main theoretical approaches to the interpretation of the concept of “financial security” and display its main components. The article is isolating the main factors in the formation of financial security in Ukraine, studies of trends and characteristics impact on the economy.Results. The study highlighted the threat of financial security, such as threats to publicsector debt policy threat, the threat of the insurance market, the threat of monetary economy, the threat of the currency market, the stock market threats and other threats. Based on statistical and other information, the analysis of safety parameters for each of the proposed components. This analysis allowed to conclude that for any of the indicators Ukraine's economy has not reached the threshold of financial security.Conclusion. Research essence of the concept of financial security allowed the state to distinguish two main approaches to its treatment: 1) emphasis on the protection of the financial interests of businesses due to the influence of internal and external factors; 2) highlights the availability of sufficient funds to meet the needs of the state, region and individual entities. The primary measures that can be used to enhance the financial security of Ukraine's economy as a whole, should be aimed at: reducing the budget deficit, lower inflation, increase in lending business structures, reducing the proportion of cash sales, increased foreign investment in the economy stabilizing the national currency, increasing the volume of financial resources for sustainable development of the economy in the long run.